1923 N.M. Laws 179, § 1 - (:unkn) unknown (My University, 1923)
Ch. 115, § 1: Any person who knowingly transports or takes into or upon any public service passenger car or passenger coach in the State of New Mexico, any bomb, dynamite, nitro-glycerine, vigorite, Giant or Hercules powder, gunpowder or other chemical compound or explosive shall be guilty of a felony and upon conviction thereof shall be punished by imprisonment for a term of not less than three years nor more than five years.
Keywords: GUNPOWDER - TRANSPORTATION